Ethnomedicinal plants of Lepcha community in Ilam district, eastern Nepal - Bhattarai, Krishna Prasad (Nepalese Journal of Biosciences, 2013)
Ilam district is situated in eastern part of Nepal and main tribes of the district are Lepcha, Rai, Limbu, Tamang, Sunuar and Gurung. The present investigation document ethnomedicinal properties of 35 species of plants belonging to 33 genera under 28 families. The plants parts are commonly used in the treatment of various diseases like pneumonia, asthma, fever, diarrhea, bronchitis, dysentery, diabetes, measles, jaundice, typhoid, syphilis, ulcer and blood pressure.